2021
DOI: 10.1136/tsaco-2020-000640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on health insurance coverage among trauma patients: a study of six level I trauma centers

Abstract: BackgroundIncreased unemployment during the COVID-19 pandemic has likely led to widespread loss of employer-provided health insurance. This study examined trends in health insurance coverage among trauma patients during the COVID-19 pandemic, including differences in demographics and clinical characteristics by insurance type.MethodsThis was a retrospective study on adult patients admitted to six level 1 trauma centers between January 1, 2018 and June 30, 2020. The primary exposure was hospital admission date:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
7
2
Order By: Relevance
“…But in subsequent surges (3, 4), all groups except those who were privately insured increased with the largest increase occurring in the Medicaid group. Our results showed Medicaid patients increased and privately insured patients decreased during the pandemic period, whereas Sercy et al 3 reported opposite trends in Medicaid and privately insured patients during the pandemic period. 3 However, Sercy et al 3 only analyzed 6 Level 1 TCs which may limit the generalizability of their results.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…But in subsequent surges (3, 4), all groups except those who were privately insured increased with the largest increase occurring in the Medicaid group. Our results showed Medicaid patients increased and privately insured patients decreased during the pandemic period, whereas Sercy et al 3 reported opposite trends in Medicaid and privately insured patients during the pandemic period. 3 However, Sercy et al 3 only analyzed 6 Level 1 TCs which may limit the generalizability of their results.…”
Section: Discussioncontrasting
confidence: 66%
“…Our results showed Medicaid patients increased and privately insured patients decreased during the pandemic period, whereas Sercy et al 3 reported opposite trends in Medicaid and privately insured patients during the pandemic period. 3 However, Sercy et al 3 only analyzed 6 Level 1 TCs which may limit the generalizability of their results. Moreover, the increase in Medicaid patients is consistent with a report from the Department of Health and Human Services (DHHS) that revealed significantly more patients enrolled in Marketplace or Medicaid coverage.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Sercy et al [34] showed a clear trend of increasing rates of uninsured patients during the pandemic. However, the rates of individuals covered by private insurance did not decline during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these anecdotal experiences and that COVID-19 had a marked effect on daily activities, unemployment level, and well-being, 6 – 8 the objective of this study was to assess temporal effects of the pandemic on trauma volume, demographics, and mechanism of injury patterns. Trauma patients admitted to our trauma center before, during, and immediately after the first wave of COVID-19 in NYC were analyzed.…”
Section: Introductionmentioning
confidence: 99%